Two-stage laparoscopic repair of two-level ureteral strictures: our experience of 8 patients - Xue, Rui-Zhi; Tang, Zheng-Yan; Zeng, Ming-Qiang; Huang, Liang; Chen, Jun-Jie; Chen, Zhi (Urology Journal, 2019)
Purpose: To evaluate the feasibility and effectiveness of two-stage laparoscopic repair for two-level ureteral strictures. Materials and Methods: From October 2010 to January 2017, 8 patients with two-level ureteral strictures, which were located in upper and lower ureter, received two-stage laparoscopic repair in our institution. Laparoscopic ureteroureterostomy was conducted for the upper ureteral strictures in first stage and 8 weeks later laparoscopic ureterovesical reimplantation was performed for lower stricture after the patency of upper lesion was confirmed by antegrade ureteropyelography. The kidney was drained by a nephrostomy tube during the interval period of two operations. Result: All the operations were performed successfully without intraoperative complications except one patient converted to open surgery during second-stage operation. For first-stage surgery, mean operating time was 120.88 ± 16.88 min, mean blood loss was 89.38 ± 13.74 mL, and mean duration of postoperative hospitalization was 3.63 ± 0.74 days. While in second-stage surgery, mean operating time took 125.25 ± 17.00 min, mean blood loss was 65.63 ± 10.16 mL, and mean duration of postoperative hospitalization was 3.62 ± 1.41 days.. On ureteropyelography 10 weeks after second-stage surgery, the contrast medium flowed from kidney down into bladder unrestrictedly and the patency of entire ureter was restored in all patients. During the follow-up, one female was observed kidney atrophy with ureteral calculus formed on the lesion side, and was successfully treated by ureteroscopic lithotripsy. No sign of stricture recurrence was found on other patients. Conclusion: Two-stage laparoscopic repair is a feasible and effective treatment for two-level ureteral strictures. But its indication is relatively narrow and confined to ureteral strictures located in two sites with sufficient interval distance and minor stricture length.